Telomere structure and maintenance gene variants and risk of five cancer types. Issue 12 (8th September 2016) - Karami, Sara; Han, Younghun; Pande, Mala; Cheng, Iona; Rudd, James; Pierce, Brandon L.; Nutter, Ellen L.; Schumacher, Fredrick R.; Kote‐Jarai, Zsofia; Lindstrom, Sara; Witte, John S.; Fang, Shenying; et al.
Abstract : Telomeres cap chromosome ends, protecting them from degradation, double‐strand breaks, and end‐to‐end fusions. Telomeres are maintained by telomerase, a reverse transcriptase encoded by TERT, and an RNA template encoded by TERC . Loci in the TERT and adjoining CLPTM1L region are associated with risk of multiple cancers. We therefore investigated associations between variants in 22 telomere structure and maintenance gene regions and colorectal, breast, prostate, ovarian, and lung cancer risk. We performed subset‐based meta‐analyses of 204, 993 directly‐measured and imputed SNPs among 61, 851 cancer cases and 74, 457 controls of European descent. Independent associations for SNP minor alleles were identified using sequential conditional analysis (with gene‐level p value cutoffs ≤3.08 × 10 −5 ). Of the thirteen independent SNPs observed to be associated with cancer risk, novel findings were observed for seven loci. Across the DCLRE1B region, rs974494 and rs12144215 were inversely associated with prostate and lung cancers, and colorectal, breast, and prostate cancers, respectively. Across the TERC region, rs75316749 was positively associated with colorectal, breast, ovarian, and lung cancers. Across the DCLRE1B region, rs974404 and rs12144215 were inversely associated with prostate and lung cancers, and colorectal, breast, and prostate cancers, respectively. Near POT1, rs116895242 was inversely associated with colorectal, ovarian, and lung cancers, and RTEL1 rs34978822 was inversely associated with prostate and lung cancers. The complex association patterns in telomere‐related genes across cancer types may provide insight into mechanisms through which telomere dysfunction in different tissues influences cancer risk. Abstract : What's new? Variants in several telomere‐related genes have been linked to cancer risk. Here the authors systematically searched for associations between >200, 000 variants in 22 of these gene regions and colorectal, breast, prostate, ovarian, and lung cancer risk utilizing a novel ASSociation analysis based on SubSET (ASSET) meta‐analytic approach. They identified several independent variants with a complex association pattern across cancer types, providing the basis for new mechanistic studies into the role of telomere structure and maintenance in cancer.